2006
DOI: 10.1016/j.jacc.2005.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparison of Upstream Tirofiban Versus Downstream High Bolus Dose Tirofiban or Abciximab on Tissue-Level Perfusion and Troponin Release in High-Risk Acute Coronary Syndromes Treated With Percutaneous Coronary Interventions

Abstract: Among high-risk non-ST-segment-elevation ACS patients treated with an early invasive strategy, upstream tirofiban is associated with improved tissue-level perfusion and attenuated myocardial damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(47 citation statements)
references
References 20 publications
1
43
1
2
Order By: Relevance
“…This result was supported by many studies which consistently reported better outcomes with upstream or early use of glycoprotein IIb/IIIa inhibitor compared with deferred treatment or other strategies (LOE 1 [452][453][454][455][456][457][458][459][460][461][462][463][464][465][466][467] ; LOE 2 468 -473 ; LOE 3 474 ; LOE 4 [475][476][477][478] ; LOE 5 479 ).…”
Section: Consensus On Sciencementioning
confidence: 74%
“…This result was supported by many studies which consistently reported better outcomes with upstream or early use of glycoprotein IIb/IIIa inhibitor compared with deferred treatment or other strategies (LOE 1 [452][453][454][455][456][457][458][459][460][461][462][463][464][465][466][467] ; LOE 2 468 -473 ; LOE 3 474 ; LOE 4 [475][476][477][478] ; LOE 5 479 ).…”
Section: Consensus On Sciencementioning
confidence: 74%
“…Previous studies of tirofiban have focused mostly on non-ST elevation ACS and their results have sometimes been inconsistent. 7,[15][16][17] The RESTORE investigators have shown in a large group of patients with unstable angina or acute MI that tirofiban reduced major cardiovascular events within 2 days following primary or nonprimary PCI; however, tirofiban did not improve the clinical outcomes or reduce coronary restenosis between day 2 and 6 months following the PCI. 15, 16 The TARGET trial, which also involved patients with unstable angina or non-ST-elevation MI, demonstrated that abciximab was superior to tirofiban in lowering the rates of MI at 30 days and 6 months; however, the 6-month mortality rates were identical for the abciximab and tirofiban groups.…”
Section: Discussionmentioning
confidence: 99%
“…Minor bleeding was defined as a fall in hemoglobin <2.0 mmol/L without the need for a blood transfusion. 7 …”
Section: Evaluation Of Therapeutic Efficacymentioning
confidence: 99%
“…7,8,[13][14][15][16][17][18][19][20][21][22] The main features of each trial are reported in Table 1. Treatment in all trials was on a background of aspirin therapy.…”
Section: Clinical Trialsmentioning
confidence: 99%